Stress, resilience, and learning in emergency: a multi-case study of children’s well-being and cognitive functioning in a West Bank refugee camp - Joma, Amjad; Arvisais, Olivier (Frontiers in Education, 2026)
Against the backdrop of ongoing conflict in the Occupied Palestinian Territories, this study investigates the complex relationship between stress, well-being, and learning in children. Utilizing a multi-case approach, researchers meticulously evaluated six children from one of the refugee camps in the West Bank. They measured variables such as exposure to potentially traumatic events, perceived stress levels, physiological stress responses, resilience, and cognitive performance to assess their findings. Despite experiencing high levels of political violence, the participants demonstrated a predominant trend toward strong resilience and overall well-being. However, significant differences emerged between self-reported stress scores and objective physiological measurements, highlighting the need for a comprehensive approach in understanding children’s experiences of stress. An evaluation of cognitive abilities demonstrated significant cognitive inhibition and difficulties with working memory and cognitive flexibility. This study illuminates the multifaceted nature of children’s responses to stress in regions affected by conflict, emphasizing the pressing necessity for customized pedagogical approaches and extensive research to improve understanding and intervention strategies.